2023
DOI: 10.7759/cureus.38645
|View full text |Cite
|
Sign up to set email alerts
|

Local Control Failure After Five-Fraction Stereotactic Radiosurgery Alone for Symptomatic Brain Metastasis From Squamous Cell Lung Carcinoma Despite 43 Gy to Gross Tumor Margin With Internal Steep Dose Increase and Tumor Shrinkage During Irradiation

Abstract: Five-fraction (fr) stereotactic radiosurgery (SRS) is increasingly being applied to large brain metastases (BMs) >2-3 cm in diameter, for which 30-35 Gy is the commonly prescribed dose. Since 2018, to further enhance both safety and efficacy, we have limited the five-fr SRS to approximately ≤3 cm BMs and adopted our own modified dose prescription and distribution: 43 and 31 Gy cover the boundaries of the gross tumor volume (GTV) and 2 mm outside the GTV, respectively, along with a steep dose increase inside th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 20 publications
(83 reference statements)
0
0
0
Order By: Relevance
“…Re-SRS in the present case was performed with curative intent, as the last opportunity to eradicate the recurrent lesion, considering the possibility of long-term survival and the presumed radio-resistance of pannegative LAC [3,9,10]. The GTV marginal dose of re-SRS in the present case seems to be one of the highest in the world: the BED 10 of 81.6 Gy is equivalent to a single fraction of 24 Gy [3,7,9].…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…Re-SRS in the present case was performed with curative intent, as the last opportunity to eradicate the recurrent lesion, considering the possibility of long-term survival and the presumed radio-resistance of pannegative LAC [3,9,10]. The GTV marginal dose of re-SRS in the present case seems to be one of the highest in the world: the BED 10 of 81.6 Gy is equivalent to a single fraction of 24 Gy [3,7,9].…”
Section: Discussionmentioning
confidence: 85%
“…Re-SRS in the present case was performed with curative intent, as the last opportunity to eradicate the recurrent lesion, considering the possibility of long-term survival and the presumed radio-resistance of pannegative LAC [3,9,10]. The GTV marginal dose of re-SRS in the present case seems to be one of the highest in the world: the BED 10 of 81.6 Gy is equivalent to a single fraction of 24 Gy [3,7,9]. Matsuyama et al have reported the significance of a BED 10 of ≥80 Gy covering 1-2 mm outside a GTV in multi-fr SRS, to ensure excellent local control of BMs in non-small lung cancer (NSCLC) [11]; this scheme has hardly been followed up or validated since 2013, and no other facilities seem to perform SRS in accordance with this policy, especially in the re-irradiation setting [1][2][3][4].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations